Relationship Age Age Mother And Pregnancy In Women With Neonatal Asphiksia In Dr. R. Goetheng Tarunadibrata Hospital - Rosi Kurnia Sugiharti (Universitas Harapan Bangsa Purwokerto, 2016)
The main causes of neonatal mortality or neonatal in the world 23% are born with neonatal asphyxia andtrauma.Faktor which is known to be the cause of neonatal asphyxia in newborns, including the factor of themother, the umbilical cord and the baby. According to a survey conducted by researchers at the HospitalGoetheng Tarunadibrata Purbalingga in 2014 there were 477 cases of neonatal asphyxia from 5680 deliveries(8.4%), then in 2015 increased to 848 from 5862 deliveries (14.5%). The purpose of this study to determine the factors maternal age and gestational age with maternal neonatalasphyxia in hospitals Goetheng Tarunadibrata Purbalingga Year 2015. This research is an analytic correlationwith sampling control.Teknik case approach in this study using a quota sampling, sample of this research is allnew babies born in hospitals Goetheng Tarunadibrata in 2015 by 100 respondents. Measuring instruments usedmaster table and type of data is secondary data. Data were analyzed using univariate and bivariate with chi-square. The results showed that there was a relationship between maternal age, gestational age with neonatal asphyxia indicated with p value of each ie (0.024) (0.032) Keywords: Factors maternal, neonatal asphyxia